Ready of not? Perceptions of the strengths and weaknesses of newly qualified medical microbiologists entering practise in South Africa - Hoffmann, Rena (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.